Exploring the Internal Structure and Rules of Irregular Patterns of Past Tense Verbs Applied in Vocabulary Acquisition by Chinese EFL Learners in UIC - Qianqing Luo (Journal of Linguistics and Communication Studies, 2024)
Morphology as a branch of linguistics, has been proven to positively promote literacy skills, especially in the area of vocabulary acquisition in the aspect of spelling and reading, for example, infection of past tenses of verbs. However, there has been a dearth of research investigating the construct and proceeding process of transformation of irregular past tenses through EFL learners. This article conducted an experimental study in an English immersion teaching university — Beijing Normal University – Hong Kong Baptist University United International College in Zhuhai, Guangdong Province, China, which examined whether the Chinese EFL learners in UIC relied on lexicon memory or minor rules based on similarity to process the past tense of irregular verbs. This study focused on revealing whether there is internal structure and rules in irregular patterns of past tense verbs being applied in vocabulary acquisition, by EFL learners in UIC through a language test consisting of 45 fill-in-blank completion sentences. We set and verified the hypothesis that minor rules based on the similarity in the irregular’s clusters, exist in the inflection of irregular verb past tense during the process of transforming by EFL learners in UIC. This study involved 20 college students, adopted the quantitative research method and analyzes data through SPSS. The findings illustrate that the participants relied on grammatical rules in the conversion of the past tense of verbs, but at the same time, some could also find the similarity or associative patterns in the past tense of irregular verbs. The results of the data analysis show that among EFL learners of UIC, this hypothesis is not tenable, but we cannot deny that minor rules based on the similarity of the irregular’s clusters exist among inflection of the irregular verb. The experimental results will be of reference significance to the systematic design of teaching of past tense verbs based on the way language learners recognize and process words.